An assessment of stakeholder perception on the development of Iskandar Malaysia: review of process and procedure - Rabe, Noor Suzilawati; Mohamed Osman, Mariana; Bachok, Syahriah (Elsevier Ltd., 2016)
This paper examines the establishment of Iskandar Malaysia development through qualitative and quantitative research methods. This paper also evaluates stakeholders’ perception on the development process and procedures in Iskandar Malaysia. Through review of literatures, semi-structured interviews and questionnaire, data were gathered. A triangulation method was then used to examine the information on a level of stakeholder participation in the development of Iskandar Malaysia. Results indicated there were conflicts between Iskandar Malaysia master plan with the development plans used in the region. Hence, the discussion on recommendation and suggestion in the article will offer several recommendations for improving regional economic development in Malaysia.